Psychological determinants of the effectiveness of conjugated linoleic acid supplementation in overweight and obese women—a randomized controlled trial - Jamka, Małgorzata; Popek, Joanna; Bukowska-Posadzy, Anna; Mądry, Edyta; Lisowska, Aleksandra; Jończyk-Potoczna, Katarzyna; Cielecka-Piontek, Judyta; Bogdański, Paweł; Walkowiak, Jarosław (Frontiers in Nutrition, 2024)
Introduction Previous studies investigating the effectiveness of conjugated linoleic acid (CLA) supplementation in body weight reduction provided unequivocal results. We hypothesized that psychological factors such as self-efficacy, locus of control or dispositional optimism can affect the success of the intervention. Therefore, this study aimed to determine the psychological factors that modulate the effectiveness of CLA supplementation in overweight or obese women and affect the ability to successfully complete the study. Methods In total, 74 subjects were recruited into this three-month randomized trial and divided into intervention and control groups receiving, respectively, capsules containing 3 g 80% CLA per day and capsules containing 3 g of sunflower oil. The following psychological tests were performed before the intervention: Multidimensional Health Locus of Control scale, Acceptance of Illness Scale, Satisfaction with Life Scale (SWLS), General Self Efficacy Scale (GSES), Health Behavior Inventory scale and Life Orientation Test (LOT-R). Results A total of 60 women completed the study and the subjects who dropped out obtained higher scores in the GSES (p = 0.0490) and the LOT-R (p = 0.0087) tests than subjects who completed the trial. Besides, multivariate linear regression demonstrated that the SWLS test (p = 0.0345) results were independent predictors of body weight changes. Conclusion In conclusion, psychological factors like self-efficacy and optimism may be associated with a higher risk of withdrawal from the study, while satisfaction with life may have an impact on the effectiveness of body weight reduction. Clinical trial registration: [https://drks.de/search/en], identifier [DRKS00010462].